2022
DOI: 10.1111/jtxs.12678
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physicochemical, rheological, and thermal properties of Indian rice cultivars: Implications on the extrusion characteristics

Abstract: The implications of physicochemical, rheological, and thermal properties of seven eminent Indian rice cultivars (PR 114, 121, 122, 123, 124, 126, and 127) on the extrusion behavior and physico-functionalities of the extrudates were investigated.The amylose and amylopectin content of the cultivars ranged between 12.72 to 28.86% and 71.14 to 87.28% in addition with protein and crude fat content that varied from 7.05 to 9.15% and 0.49 to 1.17%, respectively. The onset (r = 0.98), peak (r = 0.95), and conclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Currently, considerable efforts are ensuing to increase the nutritional value of extruded products by use of whole‐grain cereal flours (Oliveira et al, 2015), partial replacement of refined flours with whole‐grain flours (Bhati, Singh, Singh, Sharma, & Pandiselvam, 2022; Oliveira et al, 2018; Wójtowicz et al, 2015), and use of bran or fiber‐rich ingredients (Zainuddin et al, 2014), with millets and legumes (Kaur, Singh, Singh, & Sharma, 2020) and other sources of phytochemicals (Punia Bangar, Singh, Chaudhary, Sharma, & Lorenzo, 2022; Singh et al, 2016). As the use of whole‐grain flour in the preparation of extruded products is more techno‐economically feasible than enriching the refined flours with isolated bran (Wójtowicz et al, 2015), the utilization of whole‐grain cereal flours is suggested in the development of nutritious and healthy extruded breakfast cereals.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, considerable efforts are ensuing to increase the nutritional value of extruded products by use of whole‐grain cereal flours (Oliveira et al, 2015), partial replacement of refined flours with whole‐grain flours (Bhati, Singh, Singh, Sharma, & Pandiselvam, 2022; Oliveira et al, 2018; Wójtowicz et al, 2015), and use of bran or fiber‐rich ingredients (Zainuddin et al, 2014), with millets and legumes (Kaur, Singh, Singh, & Sharma, 2020) and other sources of phytochemicals (Punia Bangar, Singh, Chaudhary, Sharma, & Lorenzo, 2022; Singh et al, 2016). As the use of whole‐grain flour in the preparation of extruded products is more techno‐economically feasible than enriching the refined flours with isolated bran (Wójtowicz et al, 2015), the utilization of whole‐grain cereal flours is suggested in the development of nutritious and healthy extruded breakfast cereals.…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were reported earlier by Dala-Paula et al [ 57 ], who indicated that GABA content increased after the in vitro digestion of chocolate due to digestive enzymes, which agreed with results herein. The resistance of GABA to the gastric environment (pH 1.2) and intestinal conditions (pH 7) was also reported for GABA-rich yoghurt [ 56 ].…”
Section: Resultsmentioning
confidence: 79%
“…High values of specific mechanical energy in the extrusion process result in a positive effect on expansion, a growth of gas bubbles and a less dense and more brittle final texture [ 55 ]. BD expresses an imperative relationship with its ability to sink or float when added to any liquid such as water, milk, yogurt or dairy drink [ 56 ]. According to Figure 4 , the lowest BD values were obtained with the highest levels of CG (β 1 = 0.15, Supplementary Material, Table S1 ) and lower germinated pseudocereal flour levels (β 2 = 0.15, Supplementary Material, Table S1 ) for a higher EI.…”
Section: Resultsmentioning
confidence: 99%
“…Rice flour and corn flour in different proportions was mixed with 15% CMR, 16 and 20% feed moisture with neera honey and 16% feed moisture with water (Figure 1). During extrusion the flour is initially converted in to a viscoelastic bulk due the high pressure, shear forces, and temperature [30]. This step is followed by the entrapment of small air bubbles in the mass called nucleation where the entrapped air bubbles later expand in size as a result of the fast moisture evaporation termed as bubble growth.Finally, as the viscoelastic mass cools, the expansion of these bubbles stops.…”
Section: Neera Honey Incorporated Extrudatesmentioning
confidence: 99%